Expanding the scope of powerful electrochemical methods by exploiting nanoconfined cascade catalysis - Herold, RA (2023)
The Electrochemical Leaf (e-Leaf) extends powerful electrochemical methods, historically only applicable to a relatively small group of “electroactive” enzymes (i.e., enzymes that can directly exchange electrons with an electrode), to non-electroactive enzymes. The technology works by trapping enzymes inside a nanoporous electrode and linking the reaction(s) catalyzed by the enzyme(s) of interest to an NADP(H)-recycling enzyme, ferredoxin NADP+-reductase (FNR), which is controlled electrochemically; the outcome is that the catalytic activity of the overall enzyme cascade is simultaneously energized (via the applied electrode potential) and monitored (as electrical current) in real time. Much of this work focuses on using the e-Leaf to study wildtype isocitrate dehydrogenase 1 (IDH1) and several cancer-associated IDH1 variants. Exploiting the unique advantages of the e-Leaf for investigating slow, tight-binding inhibitors, a method and analytical framework are developed to investigate the kinetics of inhibition of a cancer-associated IDH1 variant by multiple FDA-approved drugs. Implementation of this method leads to a proposed general kinetic mechanism for allosteric IDH inhibition. Notably, the inhibition kinetics are very slow, and the data show that inhibitors can bind in both inhibitory and non-inhibitory modes. Separately, the ability of IDH1 to copurify from cells with bound NADP(H) is used to “shuttle” NADP(H) into a nanoporous electrode to create a nanoconfined NADP(H)-dependent system which can be run without any external NADP(H), i.e., only the NADP(H) that copurified bound to IDH1 is required for cascade catalysis. The system is extraordinarily stable and is able to carry out bulk electrolysis over a five-day period with an NADP(H) total turnover number of ~160,000. The presence of a finite quantity of NADP(H) in the electrode (without any NADP(H) in the bulk solution) is used to quantify concentrations of NADP(H) and IDH1 in the electrode nanopores. Together with values obtained for FNR, total nonconfined enzyme concentrations ([FNR] + [IDH1]) are shown to be ~2 mM, approaching the physical limit. At such concentrations, the average center-to-center distance between enzymes is just 9.4 nm; this leads to a “cluster channeling” effect that increases the overall enzyme cascade efficiency by preventing cascade intermediates from escaping the nanoporous electrode. Together, this work demonstrates the power of electrochemical methods for enzyme mechanistic studies and quantifies the benefits of nanoconfinement for increasing the efficiency of cascade catalysis.